Monetary Policy through Production Networks: Evidence from the Stock Market - Ozdagli, Ali; Weber, Michael (Review of Financial Studies, 2026)
Abstract We study the importance of production networks for the transmission of monetary policy using the stock market reaction as laboratory. We attribute 55% to 85% of the overall response to network effects. Large network effects are a robust feature of the data; we document similar patterns in realized fundamentals. Matching sparsity and the first two outdegrees industry-by-industry can explain large network effects. A simple model with intermediate inputs predicts the reaction of stock returns follows a spatial autoregression, which we exploit for our empirical strategy. Our results suggest production networks are an important mechanism for transmitting monetary policy shocks.